Local excision for early rectal cancer: transanal endoscopic microsurgery and beyond - Althumairi, Azah A. (J Gastrointest Oncol, 2015)
The goal of treatment for early stage rectal cancer is to optimize oncologic control while minimizing the long-term impact of treatment on quality of life. The standard of care treatment for most stage I and II rectal cancers is radical surgery alone, specifically total mesorectal excision (TME). For early rectal cancers, this procedure is usually curative but can have a substantial impact on quality of life, including the possibility of permanent colostomy and the potential for short and long-term bowel, bladder, and sexual dysfunction. Given the morbidity associated with radical surgery, alternative approaches to management of early rectal cancer have been explored, including local excision (LE) via transanal excision (TAE) or transanal endoscopic microsurgery (TEM) and transanal minimally invasive surgery (TAMIS). Compared to the gold standard of radical surgery, local procedures for strictly selected early rectal cancers should lead to identical oncological results and even better outcomes regarding morbidity, mortality, and quality of life.